Thermodynamic studies of dynamic metal ligands with copper(II), cobalt(II), zinc(II) and nickel(II). Issue 1 (2nd January 2017) - Long, S. Reid; Lin, Chung-Yon; Anslyn, Eric V.
Abstract: The self-assembly of unsymmetrical metal ligands from simpler components circumvents complex synthetic approaches. We show herein how a recently developed three-component assembly to create tripicolylamine-like ligands can be extended to the use of azides rather than pyridines. Substituent effects, metal dependence, and reversibility of the assembly are explored. Further, we show that the extent of assembly directly correlates with the differential binding of the templating metals between dipicolylamine-like and tripicolyamine-like ligands. Abstract :